Adsorption and catalytic removal of methyl orange from water by PIL-GO/TiO2/Fe3O4 composites. (February 2023) - Liu, Hongfei; Wang, Kexu; Zhang, Dongke; Zhao, Dishun; Zhai, Jianhua; Cui, Wenguang
Abstract: In this paper, an organic-inorganic hybrid material was synthesized via a simple but effective method, the novel material PGO-TiO2 /Fe3 O4 (PGTF) was produced by loading TiO2 and Fe3 O4 onto polymeric ionic liquid(PIL) functionalized graphene oxide(GO). The successful synthesis of PGTF and related structural feature were confirmed by a series of characterizations. The results of UV diffuse reflectance (DRS) demonstrated that the incorporation of PGO-Fe3 O4 to TiO2 shifted the light absorption of TiO2 from ultraviolet (UV) to visible region. The band gap energy of the PGTF reduced to1.92 eV as compared to TiO2 (3.12 eV). Different materials were used to remove methyl orange (MO) from the aqueous solution. The results showed that PGTF had a superior capacity to remove dye due to the synergistic effects of adsorption and photocatalysis. The excellent adsorption properties may result from the high specific surface area of GO and the –NH2 in the PIL. The polyionic liquid absorbed electrons due to the electrostatic action of the cation head in the polyionic liquid and GO which had high conductivity favored electron transport. The photocatalytic effectiveness increased as a result of the separation of photoexcited electron-hole pairs. The Langmuir model was investigated to evaluate the adsorption equilibrium behavior of MO dyes by PGTF. The maximum adsorption capacity( Q m ax ) was 67.88 mg/g for MO dyes. The pseudo-second-order kinetic model, with a correlation coefficient of 0.999, provided a good fit for the adsorption kinetic processes. The adsorption rate constant K2 obtained by this model is 0.0072 g/(mg*min). The degradation rate constant of PGTF for MO in the photocatalytic stage was 0.00881 min −1, which exhibited 3.7, 7.5 and 3 times higher than that of TiO2, FT and GTF. The main reactive species in the degradation process were O 2 − 、·OH、h + . PGTF had excellent repeatability because of the presence of Fe3 O4 . They can be easily separated from the water. These results indicated that the PGTF composites hold great potential for removing MO from wastewater. Highlights: Organic-inorganic composites were prepared for using of the complementary nature between organic and inorganic materials. Hybrid adsorption-photocatalysis route showed a high rate of dye pollutants removal. The presence of PIL enhances the adsorption capacity and facilitates the separation of photogenerated electrons and holes.